Understanding unwarranted variation in clinical practice: a focus on network effects, reflective medicine and learning health systems. (18th April 2020) - Atsma, Femke; Elwyn, Glyn; Westert, Gert
Abstract: In the past decades, extensive research has been performed on the phenomenon of unwarranted clinical variation in clinical practice. Many studies have been performed on signaling, describing and visualizing clinical variation. We argue that it is time for next steps in practice variation research. In addition to describing and signaling variation patterns, we argue that a better understanding of causes of variation should be gained. Moreover, target points for improving and decreasing clinical variation should be created. Key elements in this new focus should be research on the complex interaction of networks, reflective medicine, patient beliefs and objective criteria for treatment choices. By combining these different concepts, alternative research objectives and new targets for improving and reducing unwarranted variation may be defined. In this perspective, we reflect on these concepts and propose target points for future research.